Factors that confound the prediction of renal medullary oxygenation and risk of acute kidney injury from measurement of bladder urine oxygen tension. (2nd June 2019) - Ngo, Jennifer P.; Lankadeva, Yugeesh R.; Zhu, Michael Z. L.; Martin, Andrew; Kanki, Monica; Cochrane, Andrew D.; Smith, Julian A.; Thrift, Amanda G.; May, Clive N.; Evans, Roger G.
Abstract: Aim: Urinary oxygen tension (uPO2 ) may provide an estimate of renal medullary PO2 (mPO2 ) and thus risk of acute kidney injury (AKI). We assessed the potential for variations in urine flow and arterial PO2 (aPO2 ) to confound these estimates. Methods: In 28 sheep urine flow, uPO2, aPO2 and mPO2 were measured during development of septic AKI. In 65 human patients undergoing cardiac surgery requiring cardiopulmonary bypass (CPB) uPO2 and aPO2 were measured continuously during CPB, and in a subset of 20 patients, urine flow was estimated every 5 minutes. Results: In conscious sheep breathing room air, uPO2 was more closely correlated with mPO2 than with aPO2 or urine flow. The difference between mPO2 and uPO2 varied little with urine flow or aPO2 . In patients, urine flow increased abruptly from 3.42 ± 0.29 mL min −1 to 6.94 ± 0.26 mL min −1 upon commencement of CPB, usually coincident with reduced uPO2 . During hyperoxic CPB high values of uPO2 were often observed at low urine flow. Low urinary PO2 during CPB (<10 mm Hg at any time during CPB) was associated with greater (4.5‐fold) risk of AKI. However, low urine flow during CPB was not significantly associated with risk of AKI. Conclusions: uPO2 provides a robust estimate of mPO2, but this relationship is confounded by the simultaneous presence of systemic hyperoxia and low urine flow. Urine flow increases and uPO2 decreases during CPB. Thus, CPB is probably the best time to use uPO2 to detect renal medullary hypoxia and risk of post‐operative AKI.